Legal Regulations Regarding Criminal Acts of Fraud Against Civil Service Candidates Committed by Civil Servants - Bonar Yudhistira; Muhammad Arif Sahlepi; Suci Ramadani; Rahmayanti Rahmayanti; Ismaidar Ismaidar (CV. Era Digital Nusantara, 2025)
Regarding the criminal act of fraud in the recruitment of civil servants involving corrupt civil servants, the author believes that Article 378 of the Criminal Code should be maximally applied to the defendant. This crime not only constitutes an individual offense but also undermines public trust, meritocracy, and good governance principles, causing both personal and institutional harm. Hence, the sentence of 1 year and 8 months imposed on Suwari Bin Sukadar by the Mojokerto District Court (Register Number 182/Pid.B/2024/Pn Mjk) seems too light and may not effectively deter potential offenders.